NASR HAMID ABU ZAYD’S PHILOSOPHY ON ISLAM AND EDUCATION - Iwan Irwandi; Wasehudin; Erdi ruji kartawi; Agus Gunawan (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to examine Nasr Hamid Abu Zayd's philosophy of Islam and its implications for Islamic education. The research uses a qualitative approach with a library research method, through searching and critically analyzing various relevant literature, both in the form of books, scientific journal articles, and e-books that discuss Abu Zayd's thoughts, Qur'anic hermeneutics, and contemporary Islamic education philosophy. The results of the study show that Abu Zayd views the Qur'an as a text and discourse that is understood through the relationship between text, context, and interpreter, so that religious interpretation is dynamic and open. This perspective gave birth to the concept of Islamic education that is humanist, rational, dialogical, and emphasizes freedom of thought and critical awareness. This study concludes that Abu Zayd's thoughts are relevant for the development of contextual and responsive Islamic education to modern social challenges, although it still faces theological and institutional challenges in its implementation.